2014
DOI: 10.1038/jid.2013.493
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of 5-Lipoxygenase and Heme Oxygenase-1 in Wound Healing

Abstract: Lipid mediators derived from 5-lipoxygenase (5-LO) metabolism can activate both pro- and anti-inflammatory pathways, but their role in wound healing remains largely unexplored. In this study we show that 5-LO knockout (5-LO(-/-)) mice exhibited faster wound healing than wild-type (WT) animals, and exhibited upregulation of heme oxygenase-1 (HO-1). Furthermore, HO-1 inhibition in 5-LO(-/-) mice abolished the beneficial effect observed. Despite the fact that 5-LO(-/-) mice exhibited faster healing, in in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Based on the recent findings about the roles of 5-lipoxigenase (ALOX5, 5-LO) in the activation of pro-inflammatory pathways [37], we also evaluated the expression of ALOX5 in our experiments. When the treatment dosage of asafetida was increased above 10 −7 g/mL, the expression level of ALOX5 was increased in cells, which revealed that asafetida could activate pro-inflammatory signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the recent findings about the roles of 5-lipoxigenase (ALOX5, 5-LO) in the activation of pro-inflammatory pathways [37], we also evaluated the expression of ALOX5 in our experiments. When the treatment dosage of asafetida was increased above 10 −7 g/mL, the expression level of ALOX5 was increased in cells, which revealed that asafetida could activate pro-inflammatory signals.…”
Section: Discussionmentioning
confidence: 99%
“…CASP3 was selected because its activation could be triggered by both extrinsic (death ligand) and intrinsic (mitochondrial) pathways [36]. ALOX5 was selected so that we could evaluate the inflammatory responses of senescent HDFs after treatment with asafetida [37]. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, multiple studies have implicated the 5‐LOX‐LTB 4 ‐BLT1 axis in aberrant neutrophil recruitment and impaired tissue repair in experimental models of skin wound healing. In particular, 5‐LOX deficiency or pharmacological targeting of the 5‐LOX pathway resulted in accelerated cutaneous healing, likely by reducing the production of reactive oxygen species (ROS) as well as of proinflammatory cytokines and chemokines in wounded skin . Similarly, 5‐LOX‐deficient mice and mice treated with LT‐modifying drugs were protected against acute inflammatory lung injury in a model of bacterial sepsis .…”
Section: Roles Of Eicosanoids In Tissue Repairmentioning
confidence: 99%
“…Studies in 5-LOX-deficient mice showed accelerated wound healing, but the reepithelialization rates did not appear to differ between the 5-LOX and wild-type mice. 38 It is not clear whether prostanoid levels were elevated in the 5-LOX knockout mice in light of other studies that have shown shunting from the 5-LOX pathway into the COX-1/COX-2 pathway with 5-LOX inhibition. 39 Regardless, the lack of 5-LOX activity was not a detriment against wound re-epithelialization.…”
Section: Lox Productsmentioning
confidence: 76%